Double standards in body evaluation? : The influence of identification with body stimuli on ratings of attractiveness, body fat, and muscle mass - Voges, Mona M.; Giabbiconi, Claire-Marie; Schöne, Benjamin; Waldorf, Manuel; Hartmann, Andrea S.; Vocks, Silja (My University, 2019)
Although it is well documented that women evaluate their own body differently from other bodies, it remains unclear whether this discrepancy is based on double standards because of identity or on objective differences between these bodies. The aim of this study was therefore to test whether women apply double standards depending on a body's identity when evaluating the same bodies presented with different faces. Average-weight women (N = 104) rated body attractiveness, body fat, and muscle mass of thin, average-weight, overweight, athletic, and hypermuscular bodies with either another female's face or their own face. With their own face, subjects rated overweight bodies as more unattractive, higher in body fat and lower in muscle mass than with another female's face. However, for non-overweight bodies, body ratings did not differ depending on body identity. Based on the self-deprecating double standards for overweight bodies, a body-related identity bias might be considered in theoretical models of body image.Level of evidence Level V, descriptive study.
Keywords: 150